Myths of motherhood. The role of culture in the development of postpartum depression - Alessandra Ambrosini; Giovanni Stanghellini (Istituto Superiore di Sanità, 2012)
OBJECTIVES: This paper intends to offer a theoretical insight into the myths of motherhood and how these myths can bear on the pathogenesis of postpartum depression. METHODS: From a man's view motherhood is conceptualized as a necessary stage in the progress towards the attainment of femininity. This view is impersonal and external to the experience of motherhood. From a female perspective, motherhood presents itself as a conflicting situation. We will then focus on the necessity to construct a discourse on motherhood by using a code which belongs to women rather than men. The analysis of a blog and a comedy show will provide evidence concerning the evolution of the female discourse on motherhood thus contributing to the debunking of the myths of motherhood. The final section discusses ways in which myths of motherhood can bear on the pathogenesis of postpartum. CONCLUSIONS: Among "melancholic type" women, who tend to abide by social norms, play established social roles and hide their inner conflicts, myths of motherhood contribute to suppress the contradiction which is intrinsic to motherhood itself making this contradiction uncontrollable and potentially devastating.